Optimization Strategy of Budget Disbursement of the State Treasury Office of Jakarta II - Heru Priyantono; Lukman M Baga; A Faroby Falatehan (Faculty of Economics and Business Udayana University, 2017)
The objective of this research is to formulate strategies to optimize the level of budget disbursement of the State Treasury Office of Jakarta II. The analysis on budget disbursement pattern was conducted by qualitative method (descriptive) using budget realization data of the period of 2011-2015. Meanwhile, to determine the factors that influence budget disbursement, EFAS and IFAS analyses were carried out, and the results serve as the basis for preparing alternative strategies in SWOT matrix. The results show that the pattern of budget disbursement is proportional, in the sense that there is no accumulation of budget absorption at the end of the year. From the EFAS and IFAS analyses, it can be seen that there are four main strategic factors that influence the disbursement of budget of the State Treasury Office of Jakarta II i.e. (1) competent budget manager; (2) unwillingness to be a budget manager; (3) budget management training; and (4) completeness of payment documents. Optimization of budget absorption rate is formulated using a strategic architecture approach which is conducted by integrating all activities into three stages of activity implementation period. Keywords: Architecture strategy, EFAS, IFAS, budget absorption, SWOT